Political Informality: Deals, Trust Networks, and the Negotiation of Value in the Urban Realm. Issue 2 (1st February 2020) - Goodfellow, Tom
ABSTRACT: This article develops a conceptual framework for analysing political informality, before going on to explore it through a discussion of urban politics in Kampala, Uganda. It builds on recent theoretical developments concerning the relationship between 'deals' and 'rules', the role of informal trust networks in politics, and different conceptualisations of patron-client relations, to consider varying forms of informal political negotiation and bargaining. Informal politics is ubiquitous, but varies significantly in terms of its interface with formal institutions and the degree to which it is shaped by shared norms and expectations. The article draws out some of these variations through a typology setting out four partially-overlapping categories that aim to capture the diverse and dynamic nature of informal political interaction: pro-formal, anti-formal, para-formal, and a-formal. It then turns to the application of these in an urban context through an analytical discussion of marketplace politics in Kampala. The article argues that conceptualising political informality in this way can facilitate granular and comparative analyses of urban political processes often just described as 'messy', 'chaotic', or 'fluid'.